A-1-2 ファジィ推論を用いた販売促進キャラクターデザイン支援システムの開発(評価・調査分析(1)) - 白濱, 成希; 高野, 翔太 (バイオメディカル・ファジィ・システム学会大会講演論文集, 2012)
The marketing technique which performs sales promotions by adding the information relevant to a character or a character to the target goods is called mascot character strategy, and this marketing technique is used for many goods in recent years. In this study, we have developed a system that the character used as an important core in strategy mascot is generated automatically by the character design information obtained by fuzzy inference using the product images and features. As an evaluation of this study that 15 human subject of over the age of 60 from less than 10 generations saw the character that is automatically estimated of apple to be using this system and answered various questionnaire. The questionnaire results were many opinions affirmative, the individuality of the apple has been expressed well, and the same kind of apple has also designed the character which has a difference in individuality. When this study was actually used in the shop, there were many subjects who want to buy the goods advertised by the designed character. Therefore, we considered that this system is effective enough in sales promotion of goods and this study aims to be one of the ways on new technical strategy mascot.